2009
DOI: 10.1007/s10347-009-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of microbialites as contemporaneous framework components of deglacial coral reefs, Tahiti (IODP 310)

Abstract: Deglacial reefs from Tahiti (IODP 310) feature a co-occurrence of zooxanthellate corals with microbialites that compose up to 80 vol% of the reef framework. The notion that microbialites tend to form in more nutrient-rich environments has previously led to the concept that such encrustations are considerably younger than the coral framework, and that they have formed in deeper storeys of the reef edifice, or that they represent severe disturbances of the reef ecosystem. As indicated by their repetitive interbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…In particular, we have demonstrated that the aragonite grains that have been trapped in the microbialite crusts during their formation do not aVect the 14 C age of the microbialite bulk sample. However, it must be noted that the aragonitic fraction measured on 45 samples ranges from 0 to 23%, i.e., much less than the 38-68% estimates reported by Westphal et al (2010). The 14 C ages that we have obtained on corals, coralline algae, and microbialites are in good agreement and stratigraphically consistent throughout the last deglacial reef sequence.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In particular, we have demonstrated that the aragonite grains that have been trapped in the microbialite crusts during their formation do not aVect the 14 C age of the microbialite bulk sample. However, it must be noted that the aragonitic fraction measured on 45 samples ranges from 0 to 23%, i.e., much less than the 38-68% estimates reported by Westphal et al (2010). The 14 C ages that we have obtained on corals, coralline algae, and microbialites are in good agreement and stratigraphically consistent throughout the last deglacial reef sequence.…”
supporting
confidence: 55%
“…This comment aims to discuss brieXy the results (ages and observations) and the interpretations presented in the Westphal et al (2010) paper, especially in light of recent results obtained on the same drill cores by using an array of various methods (Seard et al 2011). We do not discuss below the "Origin of microbialites" section of that paper in which Westphal et al agree with our previous interpretations (see e.g., Camoin et al 1999).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of a large amount of microbialites (i.e., thrombolites) in reef structures as secondary framework is generally interpreted to represent shifts in ecological conditions towards more elevated trophic levels (e.g., Dupraz and Strasser 2002;Whalen et al 2002;Camoin et al 2006;Adachi et al 2007;Olivier et al 2007). Such environmental signiWcance of microbialites has been recently discussed in Holocene coral reefs of French Polynesia (Westphal et al 2010). From core samples, these authors observed a Wrst stromatolitic layer associated with some red algae, suggesting a microbialite growth contemporaneous to the coral growth.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, some authors consider the presence of framboidal pyrite as an indicator of the involvement of sulfate-reducing bacteria in the precipitation of the microbialites (Westphal et al, 2010). The formation of pyrite framboids in sediments requires an anaerobic environment, either within the sediment or inside a local microenvironment.…”
Section: Discussionmentioning
confidence: 99%